Penerapan desain jamban keluarga sistem perembesan - Muhammad Ardi; Faizal Amir; Bakhrani A. Rauf (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The PKM partner is the Head of Rompegading Village, representing a community that does not have a feces disposal(septic tank) that is safe for the environment. The problems of partners are: (1) partners do not have knowledge about familylatrine that are safe for the environment and the tools used, and (2) partners are not skilled at constructing family latrine that aresafe for the environment. The solutions offered are: (1) providing counseling so that have knowledge of family latrine that aresafe for the environment and the tools used, and (2) train and assist partners in constructing family latrine that are safe for theenvironment. The methods used are as follows: (1) when counseling is a lecture, discussion, and question and answer, (2) duringthe training are demonstration, discussion, and question and answer. The results of this PKM are: (1) partners have knowledgeabout family latrine that is safe for the environment, (2) partners recognize or know the tools and materials used to makeconstruction of family latrine that are safe for the environment, (3) skilled partners make construction of family latrine that aresafe for the environment, and (4) one unit of family latrine which was built in one of the houses of the target communitymembers, has been used and is functioning well.